2012
DOI: 10.1371/journal.pone.0052707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Profiling in Meningioma: Deregulated Signaling Pathways Associated with Meningioma and EGFL6 Overexpression in Benign Meningioma Tissue and Serum

Abstract: Molecular mechanisms underlying the pathogenesis of meningioma are not fully elucidated. In this study, we established differential gene expression profiles between meningiomas and brain arachnoidal tissue by using Affymetrix GeneChip Human U133 Plus 2.0 Array. KEGG pathway analysis demonstrated that PI3K/Akt and TGFβ signaling pathways were up-regulated in fibroblastic meningioma, and focal adhesion and ECM-receptor interaction pathways were activated in anaplastic meningioma. EGFL6 was one of the most up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
(50 reference statements)
3
38
1
Order By: Relevance
“…Through KEGG pathway analysis, the upregulated genes were associated with 16 signal transduction pathways and the downregulated genes were associated with 7 signal transduction pathways; these included pathways that are known to be directly associated with the development of colorectal cancer or other cancers, such as ECM-receptor interaction. ECM-receptor interaction was identified to be significantly activated in patients with meningioma (25). Other key pathways that regulate cell adhesion, migration, proliferation and survival were downregulated, and have been associated with numerous tumors, including breast and thyroid carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Through KEGG pathway analysis, the upregulated genes were associated with 16 signal transduction pathways and the downregulated genes were associated with 7 signal transduction pathways; these included pathways that are known to be directly associated with the development of colorectal cancer or other cancers, such as ECM-receptor interaction. ECM-receptor interaction was identified to be significantly activated in patients with meningioma (25). Other key pathways that regulate cell adhesion, migration, proliferation and survival were downregulated, and have been associated with numerous tumors, including breast and thyroid carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, a study of Wang et al with benign meningiomas takes attention. Wang et al demonstrated an up-regulation of TGFb signalling pathway in fibroblastic meningiomas [31].…”
Section: Discussionmentioning
confidence: 99%
“…First-strand cDNA was obtained via reverse transcription using 2 µg total RNA. The reaction was performed in 20 µl buffer containing 0.5 µg oligo(dT) [12][13][14][15][16][17][18] primer, 50 mM Tris-HCl (pH 8.3), 75 mM KCl, 3 mM MgCl 2 , 40 mM dithiothreitol, 0.5 mM deoxynucleotide triphosphate mixture, 10 units RNase inhibitor and 200 units Moloney murine leukemia virus reverse transcriptase (all from Invitrogen Life Technologies). After incubation at 37˚C for 60 min, the reaction was stopped via heating at 70˚C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…EGFL6, an extracellular matrix protein, has been found in human subcutaneous adipose tissue and is a paracrine/autocrine growth factor of adipose tissue in obesity (15). EGFL6 is overexpressed in benign meningioma tissues and serum (16). Downregulation of EGFL8 expression has been observed in gastric cancer, and is significantly correlated with high tumor-node-metastasis stage and poor prognosis in gastric and colorectal cancer (17,18).…”
Section: Molecular Characterization and Expression Analysis Of Mouse mentioning
confidence: 99%